Interactions between organic friction modifier additives. (November 2020) - Fry, Benjamin M.; Chui, Mang Yin; Moody, Gareth; Wong, Janet S.S.
Abstract: The interactions of different additives in engine oils can create synergistic or antagonistic effects. This paper studies how mixing different organic friction modifier additives affects friction reducing properties of lubricants in the boundary lubrication regime. Amines of different degree of saturation were mixed with either glycerol monooleate (GMO) or oleic acid in hexadecane. The model lubricants thus formed were characterised with Fourier-transform infrared spectroscopy. Friction tests in reciprocating motion using ball-on-disc steel-steel contacts were conducted to examine the tribological performance of these lubricants. Worn surfaces were examined using X-ray photoelectron spectroscopy. Oleic acid and oleylamine, a primary amine, were found to form a partial ionic liquid, providing synergistic friction reduction. This positive interaction reduces with increasing degree of saturation of the amine. No synergistic effect was observed between GMO and oleylamine, suggesting that GMO does not hydrolyse into a carboxylic acid within a rubbing contact in the presence of amine. Highlights: The synergistic interactions between OFM additives and amines were studied. Oleic acid and oleylamine formed a partial ionic liquid, reducing friction by 40%. Increasing saturation of amines reduced their synergistic effect with oleic acid. Glycerol monooleate (GMO) and amine did not show this synergy. GMO may not have hydrolysed into oleic acid in the presence of amine.